PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI (STUDI KASUS KANTOR DPRD PAREPARE) - Js, Rikayani; Fitriani, Fitriani; Tasrif, Tasrif (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, 2022)
The purpose of this study was to determine the effect of Job Satisfaction and Organizational Commitment on Employee Performance at the Kantor DPRD Parepare. The data collection techniques used in this study were observation and questionnaires. The research method used is a quantitative method. The results of this study indicate that job satisfaction has a positive and significant effect on employee performance at the Kantor DPRD Parepare. Job satisfaction can be assumed to be able to create feelings of pleasure, comfort in work and have a sense of satisfaction at work so that it becomes a driving factor in improving employee performance in the organization. Organizational Commitment has a positive and significant effect on employee performance at the Kantor DPRD Parepare. Organizational commitment can motivate an employee to work better and stay with the company.